2003
DOI: 10.1183/09031936.03.00005903
|View full text |Cite
|
Sign up to set email alerts
|

Predicting persistent disease among children who wheeze during early life

Abstract: This study sought to determine factors influencing the persistence of early life wheezing up to the age of 10 yrs and to create a score identifying those with the highest risk of persistent disease.Children were seen at birth, 1, 2, 4 and 10 yrs in a whole population birth cohort study (n=1,456). Information was collected prospectively on wheeze prevalence and subjects were classified into wheezing phenotypes. Early life genetic and environmental risk factors were recorded and skin-prick testing (SPT) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
155
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 18 publications
(20 reference statements)
7
155
1
3
Order By: Relevance
“…SCOTT et al [1] have commented, in the light of outcomes of their ''Isle of Wight Birth Cohort study'' (IoWBC) [2,3], on our findings on the risk factors for asthma in the Multicentre Allergy Study (MAS) birth cohort study [4]. We agree that the two studies lead to similar conclusions in regard to early origins of persistent wheezing, heterogeneity of childhood wheezing and the relevance of an atopic background.…”
supporting
confidence: 65%
“…SCOTT et al [1] have commented, in the light of outcomes of their ''Isle of Wight Birth Cohort study'' (IoWBC) [2,3], on our findings on the risk factors for asthma in the Multicentre Allergy Study (MAS) birth cohort study [4]. We agree that the two studies lead to similar conclusions in regard to early origins of persistent wheezing, heterogeneity of childhood wheezing and the relevance of an atopic background.…”
supporting
confidence: 65%
“…We have previously reported the development of a predictive index for risk of having persistent asthma up to age 10 years using information available from history and SPT responses. 23 The development of allergic disease, including rhinitis, depends on both genetic and environmental factors and their interactions. It has been suggested that heritable factors predominate over shared environmental influences in asthma, 24 and the same might be true for rhinitis because both diseases are closely linked.…”
Section: Discussionmentioning
confidence: 99%
“…With a wider timespan, we previously found prevalence for early life (in the first 4 years) wheezing of 40% at 10 years in our cohort [2]. We also showed that 37% of such early-life wheezing was still evident at 10 years as a persistent wheeze phenotype [4] associated with greater airflow limitation, bronchial hyperresponsiveness (BHR), morbidity [2] and risk of asthma death [5]. The remainder of the early-life wheezers were defined as early transient wheeze.…”
Section: Early-life Wheeze: ''The Child Is Father Of the Man''mentioning
confidence: 98%